(untitled) (Academic Journal of Internal Affairs, 2020)
In decision-making situation we select the appropriate product and/or service for us or our organization, based on various criteria, such as qualitative and quantitative evaluation and/or comparison. The selection procedure may be supplemented by a risk assessment and an overall risk level assessment. This article examines the possibilities of using risk management tools in a specific decision-making situation.